(untitled) (Bulletin KNOB, 2021)
In the period up to the end of the Second World War, 21 women in the Netherlands completed an academic architectural course. Five of these women married a fellow architect and conducted a joint architectural practice with their husband. These practices profited from the post-war reconstruction boom and, in the 1950s and ’60s, from the growing demand for housing and utilitarian buildings. Jannie Kammer-Kret, Toki Lammers-Koeleman, Jeanne van Rood-van Rijswijk, Koos Pot-Keegstra and Lotte Stam-Beese contrived to flourish in their chosen profession, and all had successful careers. The collaborative model embraced by these couples, which allowed the female partners to develop their potential to the full, was surprisingly emancipated for the time. Although a home-based office, with its combination of business with household and children, held obvious appeal for the woman, the initiative for such arrangements sometimes came from the husband. There were several variations on the respectful and equitable collaborative model, ranging from one in which each partner worked independently on their own commissions to one in which the melding of individual contributions was such that it was no longer possible to attribute designs to one or the other partner. What these models demonstrate is that the women architects did not need to depend on the name and fame of their husband but were perfectly capable of shaping their own career. The work of these women architects was strongly influenced by Nieuwe Bouwen principles as reflected in the application of a functionalist and sober formal idiom, averse to superfluous decoration. Unsurprisingly, given the professional circles they both frequented, their partners held similar architectural views. This undoubtedly contributed to mutual inspiration and possibly also to two-way influence. The output of women architects is astonishingly varied. These women responded to the spirit of the times and to the sometimes difficult economic circumstances by employing new types of dwellings, building materials and techniques, designing buildings for new groups of residents or by familiarizing themselves with the latest requirements of industrial clients or government bodies. Their portfolios encompassed commissions for utilitarian buildings as well as for the more predictable houses. Their household experience and practicality proved particularly useful in the design of private homes, residential aged care and schools, finding expression in efficient floor plans, modern furnishings and new, easy to clean materials. This is also evident in the home-cum-practice they designed for themselves, where they were able to give free rein to those principles.